CASE OF SUICIDAL HANGING IN DANGER OF BEING CONSIDERED AS A HOMICIDAL DEATH: CASE REPORT (Journal of Forensic Medicine & Toxicology, 2012)
Cases of “suicidal hanging” which meet stumbling block of disapproval of the relatives are sensitive. One such case is being presented. The case was marked by co existence of “sharp weapon injuries” that kept relatives protesting against the interpretation of “suicidal hanging”. Different interpretations of these injuries created confusions of homicide. After reading the case the reader would be convinced that “suicidal” hanging does present in an unconventional manner. Confusions deepen if weapon is not available on the day one but had to be searched out. Situation gets complicated if bleeding was present at the scene of hanging or if the evidence of bleeding had been wiped out.
Keywords: Hanging; Suicide; Sharp weapon cuts; Self inflicted cuts